2020
DOI: 10.1021/acsanm.0c02209
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Production of Graphene Nanoplatelets for Energy Storage

Abstract: The difficulty of scaling up the production of high-quality graphene nanoplatelets remains a major challenge for the graphene community and inhibits commercialization across a variety of market segments and applications. Here, we demonstrate a compressed, permeable reactor that produces graphene nanoplatelets via electrochemical exfoliation and controlled pressure. In contrast to prior controlled-volume reactors, the second-generation reactor allows for both direct control of pressure on the graphite source an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The reactor housing expands with the graphite as the reaction proceeds; this allows for high yields and scalable production. The detailed synthesis procedure for EEG sheets is reported in the previously published work 14,15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactor housing expands with the graphite as the reaction proceeds; this allows for high yields and scalable production. The detailed synthesis procedure for EEG sheets is reported in the previously published work 14,15 …”
Section: Methodsmentioning
confidence: 99%
“…Achee et al (prior work from the TAMU authors) developed a technique to overcome this hurdle by confining and compressing the parent graphite powder in a permeable and expandable membrane bag, which allows for continuous intercalation, expansion, and exfoliation of the graphite powders 14 . This process has already been proven to be scalable for producing bulk amounts of electrochemically exfoliated graphene (EEG) nanosheets 15 …”
Section: Introductionmentioning
confidence: 99%
“…GNPs/epoxy nanocomposites developed for various industrial and advanced composites applications showed potential improvements in structural, mechanical, thermal, and electrical properties. [34][35][36] GNPs integrated epoxy nanocomposites have headed to a new category of nanocomposites for advanced industrial applications. GNPs/ epoxy nanocomposites are currently gaining popularity due to their remarkable characteristics, manufacturing flexibility, low filler demand, and nanofiller cost-efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene Nanoplatelets (GNPs), which consist of multiple layers of graphene sheets, are alternative 2D materials that can be fabricated using lower-cost methods suitable for upscaling. 16,17 Due to the large aspect ratio of these 2D nanomaterials they can be used to modify polymers resulting in a notable improvement in the mechanical properties, 18 compared to neat counterparts even at relatively small loadings, 19 provided that a suitable processing technique is used that directly affects the quality of the particle dispersion. 20,21 Modeling and predicting the behavior of materials over time helps avoid extensive and time-consuming testing.…”
Section: Introductionmentioning
confidence: 99%